2020
DOI: 10.1175/jas-d-19-0303.1
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Surface Attachment Kinetic and Growth Transition Influences on Vapor-Grown Ice Crystals

Abstract: There are few measurements of the vapor growth of small ice crystals at temperatures below -30°C. Presented here are mass-growth measurements of heterogeneously and homogeneously frozen ice particles grown within an electrodynamic levitation diffusion chamber at temperatures between -44 and -30°C and supersaturations ( si) between 3 and 29%. These growth data are analyzed with two methods devised to estimate the deposition coefficient ( α) without the direct use of si. Measurements of si are typically uncertai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Recent experimental work suggests that depositional ice growth rates (Bailey and Hallett, 2002;Harrison et al, 2016;Pokrifka et al, 2020;Harrington and Pokrifka, 2021) and surface complexity (Schnaiter et al, 2016;Voigtländer et al, 2018) may be impacted by whether heterogeneous or homogeneous nucleation initiates the ice growth process. Prior to nucleation, experiments on heterogeneous ice nuclei have demonstrated surface defects on mineral dust serve as active sites for growth (Kiselev et al, 2016).…”
Section: Impacts Of Nucleation Pathways On Depositional Growth Ratesmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent experimental work suggests that depositional ice growth rates (Bailey and Hallett, 2002;Harrison et al, 2016;Pokrifka et al, 2020;Harrington and Pokrifka, 2021) and surface complexity (Schnaiter et al, 2016;Voigtländer et al, 2018) may be impacted by whether heterogeneous or homogeneous nucleation initiates the ice growth process. Prior to nucleation, experiments on heterogeneous ice nuclei have demonstrated surface defects on mineral dust serve as active sites for growth (Kiselev et al, 2016).…”
Section: Impacts Of Nucleation Pathways On Depositional Growth Ratesmentioning
confidence: 99%
“…Homogeneous nucleation instead is dependent on a phase transition leading to crystallization in supercooled aqueous droplets, which occurs spontaneously without requiring preferential nucleation sites. result of heterogeneous nucleation has been suggested to be dominated by dislocation growth (Harrison et al, 2016), whereas measurements also suggest that homogeneously nucleated ice is initially dominated by dislocations but may rapidly transition to ledge nucleation growth (Pokrifka et al, 2020).…”
Section: Impacts Of Nucleation Pathways On Depositional Growth Ratesmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, this study showed that the manner of nucleation can affect the subsequent crystalline habit. Levitation diffusion chamber studies also indicate that homogeneously frozen droplets have deposition coefficients that are distinctly different from crystals nucleated heterogeneously (Pokrifka et al., 2020). These studies suggest that some of the crystals formed from homogeneously frozen drops have deposition coefficients that evolve from high to low values during the experiment.…”
Section: Introductionmentioning
confidence: 99%